2008
DOI: 10.1111/j.1447-0349.2008.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Absconding: A review of the literature 1996–2008

Abstract: Absconding is a significant problem with potential for harm to patients or the general public. The consequences of absconding include physical harm, prolonged treatment time, and substantial economic costs. The aim of this systematic literature review is to synthesize quality literature about absconding from psychiatric facilities, identify gaps in knowledge, and make recommendations for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
108
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 40 publications
2
108
1
Order By: Relevance
“…The rate of patient absconding in various studies has been estimated at 2.5% -34% in psychiatric hospitals (12) and 0.27% -2.4% in general hospitals (1,3,13,14). Studies have shown that absconding is common among young individuals, men, drug addicts, patients admitted to emergency departments (ED), and those with imprisonment experiences (3,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of patient absconding in various studies has been estimated at 2.5% -34% in psychiatric hospitals (12) and 0.27% -2.4% in general hospitals (1,3,13,14). Studies have shown that absconding is common among young individuals, men, drug addicts, patients admitted to emergency departments (ED), and those with imprisonment experiences (3,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that absconding is common among young individuals, men, drug addicts, patients admitted to emergency departments (ED), and those with imprisonment experiences (3,(12)(13)(14)(15)(16)(17). In various studies, it has been shown that absconding occurs more frequently during warm seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Reported rates of absconding vary. In a literature review, MuirCochrane and Mosel reported absconding rates between 2.5% to 34% of all psychiatric admissions (7). Moreover, a study reported that the mean age of absconders was 31.70 years and 95.30% of absconds were male and the most of them were single (8).…”
Section: Introductionmentioning
confidence: 99%
“…Absconding from acute care psychiatric settings is a significant issue, with a review of literature by Bowers, Jarrett and Clark (1998) reporting a mean absconding rate of 12.6% (Range=2-44%), while a more recent review reported similar absconding rates between 2.5 and 34% of all admissions (Muir-Cochrane & Mosel, 2008).. This recent systematic review identified that absconding was linked to serious self-harm and harm to others, medication non-compliance, alcohol consumption, aggression and violence (Muir-Cochrane & Mosel 2008).…”
Section: Abscondingmentioning
confidence: 99%
“…This recent systematic review identified that absconding was linked to serious self-harm and harm to others, medication non-compliance, alcohol consumption, aggression and violence (Muir-Cochrane & Mosel 2008). The prevalent profile across the reviewed studies of the patient that absconded was that of a young male diagnosed with schizophrenia and detained for treatment under mental health legislation.…”
Section: Abscondingmentioning
confidence: 99%